Initiatives to Enhance Nationalism among Indonesian Migrant Workers Children in Malaysia: International Community Engagement at ICC Muar: Upaya Peningkatan Nasionalisme Anak-anak Pekerja Migran Indonesia di Malayasia: International Community Engagement di ICC Muar - Jennie Nabilah; Tsabitah Nuril Adzronnida; Putri Ismukhanah Ayu Alifia (Universitas Muhammadiyah Palembang, 2025)
The international community service program organized by UIN Sunan Ampel Surabaya students at the Indonesia Community Centre (ICC) Muar, Malaysia, aims to improve national insight and nationalism among children of Indonesian migrant workers (PMI). These children face a national identity crisis because they grow up in a Malaysian environment with limited access to formal Indonesian education. The program includes several initiatives, such as creating nationalism-themed textbooks that introduce historical figures, ethnic cultures, and Indonesian tourist destinations, and are equipped with quizzes and assignments to measure students' understanding. In addition, a Sinanggar Tulo Dance workshop and a nationalism quiz competition were held to instill pride in Indonesian culture. This study used qualitative methods, collecting data through surveys, workshops, and group discussions. The results showed a significant increase in understanding Indonesian culture and history and strengthening national identity among PMI children. This program serves as an essential model for similar initiatives in the context of migration, focusing on maintaining nationalism through education and culture.